Analysis of monthly rates of return in April and correlation analysis of monthly rates of return in April on the example of selected world stock exchange indices - Krzysztof Borowski (Institute of Economic Research (IER), 2015)
The article presents a study of effectiveness of 22 selected stock indices with the use of the rates of return in the month of April. The portfolio replicating the stock index was bought at the close prices on the last session in March, and sold at the close prices on the last session in April. The presence of market inefficiency is demonstrated in the following cases: All-Ord, AMEX, BUX, CAC40, DAX, DJIA, DJTA, DJUA, EOE, FTSE100, SMI, SP500. There was no incidence rates of return significantly different from zero while maintaining a month long investment strategy for indexes such as: B-Share, Bovespa, Buenos, Hang-Seng, MEX-IPC, Nasdaq, Nikkei, Russel, TSE and WIG. The last part of the article is dedicated to correlation coefficients of rates of return for analyzed indices in month of April.
Keywords: G11; G14; 330; market efficiency; financial market seasonality; market anomalies; April effect